1998
DOI: 10.1034/j.1600-0412.1998.771005.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of anal sphincter rupture at delivery in Sweden and Finland ‐ result of difference in manual help to the baby's head

Abstract: The difference in the incidence of anal sphincter rupture between Malmö, Sweden and Turku, Finland may be due to the difference in manual control of the baby's head when crowning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
1
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 13 publications
(13 reference statements)
7
88
1
6
Order By: Relevance
“…Investigators from Scandinavia have shown that the delivery method has a significant influence on the rate of anal sphincter tear [13]. Our data do not support this explanation.…”
Section: Discussioncontrasting
confidence: 57%
“…Investigators from Scandinavia have shown that the delivery method has a significant influence on the rate of anal sphincter tear [13]. Our data do not support this explanation.…”
Section: Discussioncontrasting
confidence: 57%
“…[Key words: Sphincter rupture; Primary sphincter repair; Anal incontinence; Anal manometry; Transanal ultrasonography] C linically detected anal sphincter tears usually occur in fewer than 3 percent (range, 0.3-6.0 percent) of vaginal deliveries. [1][2][3] The tears are treated by immediate surgical repair, but no peroperative distinction is usually made between the external anal sphincter (EAS) and the internal anal sphincter (IAS). Persistent anal incontinence following this procedure exceeds 40 percent in most studies (range, 20-60 percent).…”
mentioning
confidence: 99%
“…In Norway, the OASIS rate has increased from <1% in the 1960s to 4.3% at the beginning of the past decade 16,17 . A similar increase has been noted in other European countries, with the exception of Finland where the OASIS rate has remained stable at less than 1% over the past 25 years 18,19 . It is considered that this increase is secondary to the increased incidence of instrumental deliveries, improved training for health professionals and changing maternal-fetal risk factors.…”
mentioning
confidence: 52%